Lightweight Traceability for the Agile Architect. - Gayer, Sebastian; Herrmann, Andrea; Keuler, Thorsten; Riebisch, Matthias; Antonino, Pablo Oliveira (Computer (00189162), 2016)
Although traceability information is vital to many software engineering activities, agile development approaches rarely use it because of the extra effort required. In this industry case study, the authors report the results of applying their lightweight semiautomated method that integrates traceability into software architecture developed with an agile process like Scrum.